Hemispheric Differences and Spatial Ability in Robot to Human Tactile Communication. (September 2013) - Descheneaux, Charles R; Reinerman-Jones, Lauren; Barber, Daniel
Robots are following an evolutionary path similar to computers. One obstacle for this evolution is language interaction between humans and robots. Traditionally, human-to-robot language has been one way in the form of commands from human to robot. One path of robot-to-human language is tactile. Tactile communication affords the user a hands-free method of interaction. Hands-free tactile communication is an asset for military ground personnel allowing the hands, eyes, and ears to be fully utilized for other tasks. Speech and language are traditionally associated with the left cerebral hemisphere. Since tactile communication does not include the traditional auditory pathway of verbal language, there is potential for employing a more right cerebral hemisphere spatial pathway. The present study looks at the right and left cerebral hemispheric activity measured by an electroencephalogram of participants using a vibrotactile belt for robot to human communication.